An Unusual Etiology for Elevation of Activated Partial Thromboplastin Time (aPTT) in SLE: Acquired Hemophilia and Lupus Anticoagulant - Srikanth Seethala; Nathaniel P. Collins; George Comerci (Case Reports in Hematology)
A 60-year-old female who has a history significant for diabetes, depression, and rheumatoid arthritis presented with a progressively enlarging hematoma of the left upper extremity. She was found to have an enlarging hematoma and an isolated elevation of activated partial thromboplastin time (aPTT). Lab work-up revealed low factor VIII activity levels and inhibitor titers at 13.38 Bethesda units (BU). Dilute Russell’s viper venom time (dRVVT) revealed a lupus anticoagulant. Hemostasis was achieved with factor VIII inhibitor bypassing activity (FEIBA) and inhibitor eradication with-rituxan after the failure of first-line treatment with cyclophosphamide and prednisone.